2016
DOI: 10.1111/dth.12394
|View full text |Cite
|
Sign up to set email alerts
|

Topical imiquimod in the treatment of extramammary Paget's disease: A 10 year retrospective analysis in an Asian tertiary centre

Abstract: Extramammary Paget's disease (EMPD) is a rare intraepithelial adenocarcinoma usually found in apocrine-rich areas. Although surgery remains standard treatment, topical imiquimod has emerged as a promising drug for the treatment of EMPD in recent years. We present our experience in treating EMPD in Asian skin successfully with topical imiquimod 5% cream, over the past 10 years in our tertiary institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Extramammary Paget disease is associated with a high rate of local recurrence after surgery [7], which is attributed to the difficulty of determining margin status due to the EMPD’s multifocal pattern of growth, tendency to arise as an ill-defined non-mass lesion, and frequent extensive subclinical extension. Non-surgical treatment options for EMPD include topical imiquimod [33], photodynamic therapy, radiation therapy, carbon dioxide therapy, anti-androgen therapy, targeted anti-HER2/neu therapy (trastuzumab) [34,35], and cytotoxic chemotherapy [7,36]. Currently, there is no widely accepted treatment regimen for metastatic EMPD, and case studies and reports have shown that the systemic chemotherapy-based regimens used in the past had limited success.…”
Section: Discussionmentioning
confidence: 99%
“…Extramammary Paget disease is associated with a high rate of local recurrence after surgery [7], which is attributed to the difficulty of determining margin status due to the EMPD’s multifocal pattern of growth, tendency to arise as an ill-defined non-mass lesion, and frequent extensive subclinical extension. Non-surgical treatment options for EMPD include topical imiquimod [33], photodynamic therapy, radiation therapy, carbon dioxide therapy, anti-androgen therapy, targeted anti-HER2/neu therapy (trastuzumab) [34,35], and cytotoxic chemotherapy [7,36]. Currently, there is no widely accepted treatment regimen for metastatic EMPD, and case studies and reports have shown that the systemic chemotherapy-based regimens used in the past had limited success.…”
Section: Discussionmentioning
confidence: 99%
“…Topical imiquimod has shown promise as a viable alternative to surgery. By stimulating the production of multiple cytokines, imiquimod activates the immune system to create an antitumor effect . Multiple studies have reported topical imiquimod 5% cream to be effective for EMPD, with response rates ranging from 52% to 100%, and recurrence rates up to 20% .…”
Section: Nonsurgical Interventionsmentioning
confidence: 99%
“…By stimulating the production of multiple cytokines, imiquimod activates the immune system to create an antitumor effect . Multiple studies have reported topical imiquimod 5% cream to be effective for EMPD, with response rates ranging from 52% to 100%, and recurrence rates up to 20% . In a recent prospective study by Sawada et al ., the response rate with imiquimod was 100%, with five of nine patients achieving complete response (complete clinical or histopathological remission).…”
Section: Nonsurgical Interventionsmentioning
confidence: 99%
“…Imiquimod was evaluated by 13 studies (8 cohort studies, 5 case series) in 110 patients. CR was documented in 54% of patients, and 85% achieved clinical regression of 50% or more [43][44][45][46][47][48][49][50][51][52][53][54]60]. Given the propensity of EMPD for recurrence, posttreatment histological evaluation is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…Imiquimod is an immune response modifier that stimulates innate immune pathways (via induction of inflammatory cytokines, such as IFN-α, IL-6, and TNF-α) and adaptive immune pathways, resulting in an antitumor effect [59]. Eight cohort studies (3 prospective, 5 retrospective) and 5 case series (total 110 patients) investigated the effectiveness of imiquimod for EMPD at dose schedules ranging from daily to twice weekly for a duration of 2-56 weeks [43][44][45][46][47][48][49][50][51][52][53][54]60]. Overall, 54% (95% CI, 40-67%; I 2 = 37%) of patients achieved complete response (CR) and 85% (95% CI, 74-90%; I 2 = 0%) achieved clinical regression of 50% or more.…”
Section: Imiquimodmentioning
confidence: 99%